FOREIGN TERRORIST FIGHTERS AS A POTENTIAL SECURITY PROBLEM OF THE REPUBLIC OF SERBIA - Djoric, Marija; Obrenović, Strahinja (Serbian political thought, 2024)
The paper analyzes the phenomenon of foreign terrorist fighters, who can represent a potential security problem for the Republic of Serbia. It is believed that in the period from 2012 to 2016, more than 1,200 people from the Western Balkan region (including Serbia, as well). The fact that 49 Serbian adult citizens went to Syria (37 men and 12 women) is very important. Authors first made a distinction between the terms foreign fighters and foreign terrorist fighters, so that in the continuation of the work the focus would be on the classification of this phenomenon. Although foreign fighters appeared much earlier, the focus of this research is on the war in Syria, which involved a large number of international actors, including terrorist organizations, such as the „Islamic State”. The central part of the work is dedicated to the institutional and strategic framework of the Republic of Serbia, which deals with the prevention and fight against violent extremism and terrorism. In addition, the authors analyzed all potential phases (and at the same time the problem) of the return of foreign terrorist fighters, as well as their families in the territory of the Republic of Serbia, giving predictive analyses. The return of foreign terrorist fighters from Syria and Iraq to the territory of the Republic of Serbia can represent a kind of security problem. This phenomenon has been unknown until now, especially when it comes to group face restoration. In addition, this is not only about one category (eg terrorists), but we will also meet with women and children. Up until now, in the region, women have mostly been viewed as victims, but it should be borne in mind that individual members of the female gender can also be radicalized, which can have a negative impact on children as well, through the process of education. Due to all these facts, a multidisciplinary approach to this problem is necessary, which will involve experts from different fields.